Fabrication of Black Silicon With Thermostable Infrared Absorption by Femtosecond Laser - Chun-Hao Li; Ji-Hong Zhao; Xin-Yue Yu; Qi-Dai Chen; Jing Feng; Hong-Bo Sun (IEEE Photonics Journal, 2016)
Annealing-insensitive black silicon with high absorption below the silicon bandgap has been achieved by femtosecond laser direct writing. Spike microstructures with sizes ranging from 4 to 25 μm are formed on the surface layer of silicon substrate, and a large amount of phosphorous impurities ( $10^{21}\,{\rm{cm}}^{- 3}$ ) is doped during the resolidification process. The infrared absorption of phosphorus-doped black silicon decreases slightly with both the annealing temperature and duration. Excitingly, the largest decrease is less than 10% at 2 μm (annealing 240 min at 873K). This thermostable infrared absorption is related to free carrier absorption. After laser irradiation, the phosphorus-doped layer maintains a relatively high crystallinity that can be improved further during thermal annealing. The density of the electrically activated impurities is approximately $10^{19}\,{\rm{cm}}^{- 3}$ .